Charakterystyka stosunków nefologicznych w Moskwie - Szyga-Pluta, Katarzyna (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2014)
The aim of the present study was to characterize the cloudiness in Moscow. The analysis was based on the eight diurnal observations carried out in the Meterological Observatory of the Łomonosow University in Moscow in years 1974–1990. The structure of the cloudiness, annual and diurnal courses were taken upon consideration. The average annual total cloudiness is much higher in cold part of the year. The long-term variability of total cloud cover in Moscow has shown an increasing tendency. The most frequent cloud type was Stratocumulus, which dominates during the whole day.
Keywords: cloudiness; cloud types; Moscow